Caffeine Consumption and General Health in Secondary School Children: A Cross-sectional and Longitudinal Analysis - Richards, Gareth; Smith, Andrew P. (Frontiers in Nutrition, 2016)
Although caffeine is sometimes associated with beneficial effects in adults, concern has been expressed that the substance may be dangerous if intake is too high, and particularly so when used by children and adolescents. For this reason, the current study examined data from the Cornish Academies Project to determine whether caffeine consumption in secondary school children was related to responses to a single-item measure of general health. Because two cross-sections of data were available, these relationships were explored both cross-sectionally and longitudinally. High caffeine consumption (i.e. >1000 mg/w) was associated with low general health in both cross-sections of data. However, after controlling for additional aspects of diet, demography, and lifestyle, this effect only remained significant at the latter time-point. Further to this, null findings from cross-lag and change-score analyses suggested that caffeine and general health were unlikely to be causally linked in this sample. However, due to methodological limitations, such as the two cross-sections of data being collected only six months apart, it is suggested that further longitudinal and intervention studies are required in order for firm conclusions to be drawn.